Co-Creation Capability Spectrum for Classification and Scaling of Processing Services - Lazarus, Davis; Krishna, Anupam; Dhaka, Sunishtha (Prabandhan: Indian Journal of Management, 2015)
Co-creation capabilities can be used as a strategic business logic that portrays in creating superior relations between consumers and firms as a source of competitive advantage for organizations. Capabilities could be used for enhancing value co-creation for mutual and long-term betterment. The authors developed a conceptual matrix of willingness and unwillingness in terms of co-creation using in depth literature review. Conceptualizing capabilities provide a foundation of bridging a co-creation continuum with various capabilities and processing services to attain the level or extent of consumer interaction. This article also sets out an agenda for future research.